1992
DOI: 10.1055/s-2008-1033028
|View full text |Cite
|
Sign up to set email alerts
|

Bestimmung der zerebralen Dopamin–(D2)–Rezeptoren–Dichte mit Hilfe der123Jod–IBZM–SPECT bei Patienten mit Morbus Parkinson

Abstract: An alteration of the dopaminergic nigrostriatal system is believed to be the main pathogenetic factor of Parkinson's disease (PD). We report on our initial results on the determination of the post-synaptic dopamine-D2-receptor binding of 123I-IBZM in patients with PD. Drug-native patients showed a significantly higher IBZM binding in the basal ganglia as compared to patients on specific dopaminergic medication. Age, duration of the disease and the severity of the disease do not seem to influence the IBZM-recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Seit der E i n f ü h r u n g von 123 I-IBZM, einem Benzamidderivat, das eine hohe Affinität und Spezifität zu Striatalen D o p a m i n -D 2 -R e z e p t o r e n aufweist, wurde es jedoch möglich, mit Hilfe der S P E C T die regionale zerebra- le Rezeptorverteilung bildlich darzustellen (14,15). Eine Reihe von Studien konnte die klinische Wertigkeit der Rezeptorszintigraphie mit Hilfe der SPECT belegen (8,9,21,22…”
Section: Hirn-spect Mit 123 I-lisurid Bei Morbus-parkinson-patienten unclassified
See 2 more Smart Citations
“…Seit der E i n f ü h r u n g von 123 I-IBZM, einem Benzamidderivat, das eine hohe Affinität und Spezifität zu Striatalen D o p a m i n -D 2 -R e z e p t o r e n aufweist, wurde es jedoch möglich, mit Hilfe der S P E C T die regionale zerebra- le Rezeptorverteilung bildlich darzustellen (14,15). Eine Reihe von Studien konnte die klinische Wertigkeit der Rezeptorszintigraphie mit Hilfe der SPECT belegen (8,9,21,22…”
Section: Hirn-spect Mit 123 I-lisurid Bei Morbus-parkinson-patienten unclassified
“…Durch die stabile Markierung mit 1 2 3 I wird die Substanz bei gleichzeitigem Verlust der dopaminergen Eigenschaften für die SPECT brauchbar. Der Vorteil des 1 2 3 I-Lisurid gegenüber dem bereits eingeführten 1 2 3 I-IBZM (1,8,9,22) besteht in der Verfügbarkeit des nichtmarkierten Analogons Lisurid und somit der Möglichkeit, Rezeptorverdrängungs-Untersuchungen mit chemisch eng verwand-ten Liganden durchzuführen. Diese Untersuchungen können Informationen über dynamische Veränderungen der Striatalen Bindung von 1 2 3 I-Lisurid geben, die wiederum Rückschlüsse auf die Rezeptorkinetik striataler Dopamin-D2-Rezeptoren liefern könnten.…”
Section: /142unclassified
See 1 more Smart Citation
“…2 In later stages, also postsynaptically, reductions of D 2 R binding become apparent. 3 Similarly, in vivo studies indicate both a decrease of DAT 5 and an increase of D 2 R binding in depressive patients. 6 A further example is the effect of synaptic dopamine on postsynaptic D 2 R binding upon challenge with psychostimulants such as methylphenidate: Volkow and collaborators 8 demonstrated that this substance blocks the presynaptic DAT with the resulting increase of synaptic dopamine leading to a reduction of free postsynaptic D 2 R.…”
mentioning
confidence: 98%
“…Investigations of dopamine transporter (DAT) and dopamine D 2 receptor (D 2 R) binding have yielded evidence that various neurological and psychiatric conditions such as Parkinson's disease, [1][2][3] schizophrenia, 4 depression, 5,6 attention-deficit/hyperactivity disorder, 7 and drug abuse 8 are related to dysfunctions of the dopaminergic system.…”
mentioning
confidence: 99%